Pengaruh Model Learning Cycle 7E Berbantuan Buku Saku Fisika Terhadap Kemampuan Berpikir Kritis Peserta Didik - Hidayatul Iman; Sutrio Sutrio; Hikmawati Hikmawati (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
This study aims to determine the influence of the Learning Cycle 7E model with pocketbook assistance on the critical thinking skills of class X learners. This type of research uses quasi-experimental methods (pseudo experiments) with untreated control group research design with pre-test and post-test design. The population in this study is all X-class learners.  Sampling was done with purposive sampling techniques and obtained class X-MIA 3 as the experimental class and X-MIA 5 as the control class. Experimental classes are treated in the form of a 7E learning cycle model assisted by pocket books, while conventional learning control classes. The instrument used is in the form of a description test with as many as 8 questions that have been tested for validity, reliability, and different power and difficulty levels. The research hypothesis was tested using a t-test polled variant. Data analysis shows which is 7,940 > 1,678 which means Ho was rejected and Ha accepted, so it can be concluded that there is an influence of the pocketbook-assisted learning cycle 7E model on the critical thinking skills of students.